The Characteristic of Egg Drop Syndrome Virus of Medan Isolate - Kencana, Gusti Ayu Yuniati; Suartha, I Nyoman; Nurhandayani, Arini; Syamsidar, Syamsidar (Journal of Veterinary and Animal Sciences; Vol 1 No 1 (2017)DO - 10.24843/JVAS.2017.v01.i01.p04, 2017)
Egg Drop Syndrome (EDS) is a poultry disease marked by a decrease of egg production up to 40% with a declined quality of eggs. In Indonesia, EDS is astrategically infectious disease that must be eradicated. Until now, EDS vaccines are available, vaccinations on egg-laying chicken have been conducted nevertheless the case of EBS are still found. This research collaborates with PT Sanbio Laboratories (Poultry vaccine producer in Bogor) aimed to prepare EDS seed vaccines from local isolates. Isolate samples are collected from ten egg-laying chicken farmswith signs of declined production and egg quality as well as unevenly shaped and thinning of egg shells. Virus isolation was conducted on embryonated duck eggs at the age of 11 days through the allantoic space. Embryonated duck eggs are then incubated for 3 days in the incubator at 370C and are observed daily. On the third day, the eggs are taken out of the incubator and then inserted in the cooler overnight. The allantoic fluid is harvested on the third day post inoculation; it is identified with haemaglutination test and Polymerase Chain Reaction (PCR). Six isolates are positively identified as EDS virus: two from the Medan isolates, there from the Rumpin isolates, and one from Surabaya isolate. One isolate is chosen; which was the EDS isolate of Medan, with the highest titer for passaging and characterization. The content of the virus is calculated with Reed and Muench formula and expressed in a unit of Egg Lethal Dose 50 (ELD50). Research results shows titer of Medan EDS virus isolate after the second passage was 1012 HA Unit, with virus content of 109,5 EID50, length base product of PCR that was successfully amplified as 500bp. Therefore the Medan isolate is a recommended candidate for EDS vaccine seeds.